Herb–Drug Interactions Between Common Indonesian Medicinal Plants and Cardiovascular Medications: A Narrative Review - Aditya Sindu Sakti; Gumilar Adhi Nugroho; Febrika Wediasari; Muhammad Adil Khan; Muhammad Subhan A. Sibadu (Journal of Health Sciences, Medicine, Biotechnology, and Pharmaceutical Research, 2025)
The simultaneous use of herbal medicines and cardiovascular drugs is prevalent in Indonesia, a country rich in ethnomedicinal diversity. However, such combinations may lead to clinically significant herb–drug interactions, potentially compromising therapeutic efficacy and safety. This narrative review aims to summarize and evaluate the pharmacokinetic and pharmacodynamic interactions between commonly used Indonesian medicinal herbs and cardiovascular agents. A comprehensive literature search was conducted using PubMed, Scopus, ScienceDirect, and Google Scholar. The included studies reported interactions involving cytochrome P450 modulation, P-glycoprotein activity, and receptor-level mechanisms. Medicinal plants such as Panax ginseng, Allium sativum, Ginkgo biloba, Glycyrrhiza glabra, Zingiber officinale, and Cassia species were found to affect drug absorption, metabolism, and bioavailability. These interactions, primarily through CYP3A4 and P-gp modulation, altered the pharmacokinetic profiles of drugs such as warfarin, digoxin, verapamil, and simvastatin. Some herbs also exert synergistic or antagonistic pharmacodynamic effects, particularly against anticoagulants and antihypertensives. Given the chronic nature of cardiovascular therapy, herb–drug interactions pose serious clinical concerns. Enhanced awareness and monitoring are essential to prevent adverse events and therapeutic failure. Further research is needed to establish safe and evidence-based integration of herbal medicines into cardiovascular care.